Development of Robotic Arm Controller Using Arduino Microcontroller and Mobile Device Application - Nanang Ali Sutisna; Muhammad Irfan Satria (Departemen Teknik Mesin, Fakultas Teknik, Universitas Diponegoro, 2022)
In today's world, automation is widely used in many aspects to help humans do their job and increase the efficiency of the job. The robot is one of the kinds of an automation system that mostly used to help human to completed their job. Robots have many roles in human life, and robots are used to help humans do various kinds of jobs more easily. Robots are widely used because they can make it easier and done the work effectively and efficiently. There are many implementations of the robot to help humans do their jobs, such as welding robot, agriculture robot, drone robot, and many more. A robot arm is one type of robot that we often encounter, and a robot arm has a function similar to a human arm. In its application, the robot can be controlled through several methods, some are directly using a cable connection, and some are using a wireless method. Also, to control a robot, a controller is needed, which will be the robot's brain. This project aims to develop a controller based on Arduino, one of the most widely used microcontroller boards for education, hobby, or professional, and develop a mobile device application to control the robot arm via Bluetooth connection. The methodology used in this research is starting from the identification and data collection of the program from several sources such as a journal or discussion forum, then continue with the systems schematic design of the hardware that used in this project and will continue by the program of the Arduino and smartphone app. The testing result shows the accuracy of actual motion is quite close to the desired position as programmed, and the servo test shows that the error value average is about 3,54% for the MG996R servo and 4,44% for the SG90 servo. Thus, the robot error value is about 1,38% on the x-axis and 12,14% on the y-axis in the first test. And for the second test is about 1,96% on the x-axis and 3,15% on the y-axis.